Bcl6 controls meningeal Th17–B cell interaction in murine neuroinflammation - Hartlehnert, Maike; Börsch, Anna-Lena; Li, Xiaolin; Burmeister, Miriam; Gerwien, Hanna; Schafflick, David; Heming, Michael; Lu, I-Na; Narayanan, Venu; Strecker, Jan-Kolja; Kolz, Anna; Peters, Anneli; et al. (Proceedings of the National Academy of Sciences, 2021)
Ectopic lymphoid tissue containing B cells forms in the meninges at late stages of human multiple sclerosis (MS) and when neuroinflammation is induced by interleukin (IL)-17 producing T helper (Th17) cells in rodents. B cell differentiation and the subsequent release of class-switched immunoglobulins have been speculated to occur in the meninges, but the exact cellular composition and underlying mechanisms of meningeal-dominated inflammation remain unknown. Here, we performed in-depth characterization of meningeal versus parenchymal Th17-induced rodent neuroinflammation. The most pronounced cellular and transcriptional differences between these compartments was the localization of B cells exhibiting a follicular phenotype exclusively to the meninges. Correspondingly, meningeal but not parenchymal Th17 cells acquired a B cell–supporting phenotype and resided in close contact with B cells. This preferential B cell tropism for the meninges and the formation of meningeal ectopic lymphoid tissue was partially dependent on the expression of the transcription factor Bcl6 in Th17 cells that is required in other T cell lineages to induce isotype class switching in B cells. A function of Bcl6 in Th17 cells was only detected in vivo and was reflected by the induction of B cell–supporting cytokines, the appearance of follicular B cells in the meninges, and of immunoglobulin class switching in the cerebrospinal fluid. We thus identify the induction of a B cell–supporting meningeal microenvironment by Bcl6 in Th17 cells as a mechanism controlling compartment specificity in neuroinflammation.